PERANCANGAN KONTEN DIGITAL PROMOSI MUSEUM SULTAN MAHMUD BADARUDDIN II PALEMBANG DALAM ERA NEW NORMAL - Erica Albertina S; Sri Maharani Budi; Albe Gusti; Dirsha Lazuardini (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2020)
Palembang is one of the cities in the province of South Sumatera, where there are numerous aspect of tourism in this city. Palembang has a fairly long river namely Musi River. Ampera Bridge as one icon of Palembang city crosses the river. There is also a tourism spot namely Sultan Mahmud Baharuddin II Museum nearby. A museum is a storage place for historical objects. Not solely for storing such objects, you can study their history and the events underlying which able to increase your knowledge. The media used in promotion during this new normal era such as today is social media, where the medium is affordable yet highly impacful. As new normal as it is today, prospective tourists would like to spend more time at home. In case if the museum carries out a promotion, the message to be conveyed is in their hands immediately; and they will find it easier to access the information if it is carried out through that way. The promotions in new normal era are carried out through hard sell messages, where the information delivery is continuing even in such period. Education and important information has become the main content in promoting the Sultan Mahmud Badaruddin II Museum in this new normal era. This study uses the theory of social media advertising, where the promotion done in the new normal time is through instagram social media.